Energy audit for the UMP library and energy efficiency project proposal - Ahmad Syakir, Mohamad (2008)
Nowadays, people are more concerned about energy efficiency, energy consumption and conservations in buildings. Energy audit is considered as one of the comprehensive methods in checking the energy usage and wastage in buildings. This paper presents the preliminary study of energy audit that has been done in UMP library. In this study, energy audit and energy consumption data has been logged over a period of time by installing a data logger at the library main switch board. Based on the study, the actual implementation of energy efficiency programmed is done by installing capacitor bank at main switch board to improve the power factor, reduce the current consumption, voltage drop and electrical energy losses. Also reported in detail in this paper is the comparison study of energy usage and power variations over a period of time between existing and proposed techniques. From the analysis, it was found that the level of energy efficiency in building is inversely proportionate to the energy losses that occur; the higher the loss, the lower the efficiency. Energy efficient can be achieved by controlling the maximum demand and reducing energy losses by improving the power factor at the switch board. The simple pay back period calculation and formulation of the energy audit programmed for UMP library is also discussed in this paper. This paper also discuss about the improvement of lighting system efficient.